Accuracy of adrenal imaging and adrenal venous sampling in diagnosing unilateral primary aldosteronism. (7th April 2017) - Ladurner, Roland; Sommerey, Sandra; Buechner, Stefan; Dietz, Anna; Degenhart, Christoph; Hallfeldt, Klaus; Gallwas, Julia
Abstract: Introduction: The correct differentiation between unilateral and bilateral adrenal involvement in patients with primary aldosteronism (PA) is of utmost importance to justify surgical treatment. The aim of this study was to determine the accuracy of adrenal imaging compared to adrenal venous sampling (AVS), histopathology and postoperative outcome. Methods: The data of all patients with unequivocal AVS who underwent unilateral laparoscopic adrenalectomy for primary aldosteronism between May 2004 and April 2015 were entered in this retrospective study. We compared computed tomography (CT) and magnetic resonance imaging (MRI) results with corresponding AVS data, histopathology findings and postoperative outcome. Results: A total of 175 patients underwent unilateral laparoscopic adrenalectomy for primary aldosteronism. AVS was successful in 152 patients and postoperative outcome available in 148 patients. Despite unilateral disease according to AVS results, bilateral normal glands were seen in 15 MRI (17·2%) and 7 CT scans (8·5%), respectively. Unilateral enlargement of the nonhypersecreting adrenal gland was found in three MRI (3·5%) and 10 CT scans (12·2%) of patients who showed aldosterone hypersecretion deriving from the contralateral gland. Fifteen MRI (17·2%) and 18 CT scans (22·0%) revealed bilateral adrenal pathology despite unilateral aldosterone hypersecretion. Conclusion: The accuracy of CT and magnetic resonance imaging in predicting unilateral disease is poor. AVS appears to be an essential diagnostic step to identify those patients who may benefit from unilateral adrenalectomy.